2022
DOI: 10.3389/fmicb.2022.822369
|View full text |Cite
|
Sign up to set email alerts
|

d-Alanylation of Lipoteichoic Acids in Streptococcus suis Reduces Association With Leukocytes in Porcine Blood

Abstract: Streptococcus suis (S. suis) is a common swine pathogen but also poses a threat to human health in causing meningitis and severe cases of streptococcal toxic shock-like syndrome (STSLS). Therefore, it is crucial to understand how S. suis interacts with the host immune system during bacteremia. As S. suis has the ability to introduce d-alanine into its lipoteichoic acids (LTAs), we investigated the working hypothesis that cell wall modification by LTA d-alanylation influences the interaction of S. suis with por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Of note, this study demonstrates IgM BCR cleavage on different B cell populations in vitro but it remains to be shown that the IgM BCR is cleaved during infection in vivo and that this is of biological relevance. As S. suis is known to bind efficiently to different porcine immune cells present in porcine blood ( 51 ), we consider it likely that IgM BCR cleavage occurs in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, this study demonstrates IgM BCR cleavage on different B cell populations in vitro but it remains to be shown that the IgM BCR is cleaved during infection in vivo and that this is of biological relevance. As S. suis is known to bind efficiently to different porcine immune cells present in porcine blood ( 51 ), we consider it likely that IgM BCR cleavage occurs in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The relative surface hydrophobicity of ST1 GX strains was investigated by measuring their absorption to n-hexadecane, following the procedure outlined in a previous study with minor modifications [ 21 ]. In brief, bacteria were cultured overnight in 10 mL of sterile LA broth at 37°C with 5% CO 2 , harvested by centrifugation, washed three times with 5 mL of PUM buffer, and resuspended into a bacterial suspension with an optical density (OD) value of 0.6 (OD 660nm ) with PUM buffer.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted the MATH assay as described previously by Öhlmann et al [ 50 ] to compare hydrophobicity of the S. suis strains investigated in the bactericidal assay with the hydrophobicity of S. suis cps 2 strain 10 and its unencapsulated isogenic mutant 10 cps ΔEF.…”
Section: Methodsmentioning
confidence: 99%